Design Guidelines of Stacked Dual-Band SIW Slot Array With Optimal Aperture Reuse Ratio and High Aperture Efficiency - Yihong Su; Yulei Yang; Xian Qi Lin; Yong Fan (IEEE Open Journal of Antennas and Propagation)
With the advent of Internet of Things (IoT) technology, intelligent devices have greatly enhanced people’s daily lives by providing greater convenience, efficiency, and connectivity. In this context, communication between vehicles, as well as between vehicles and satellite navigation systems, base stations, and other infrastructures, is crucial. These communications utilize millimeter wave frequency bands to achieve faster response times and more accurate target tracking and identification. In this paper, the design guidelines of a stacked dual-band (28/35 GHz) substrate integrated waveguide (SIW) slot antenna array are proposed to achieve the optimal aperture reuse ratio and high aperture efficiency. The dual-band array consists of two-layer substrates, and each layer acts as an independent SIW slot antenna array. The upper substrate is composed of nonadjacent SIW slot sub-arrays for the high band operation, while the low band array is located in the lower substrate radiating through the gap between the high band sub-arrays. A dual-band antenna array with an $8× 8$ array in each band is designed and demonstrated as an example, where the center frequencies of the two bands are chosen to be 28 GHz and 35 GHz. The maximum aperture reuse ratio is achieved by the rational array arrangement, and the improvement in aperture efficiency is accomplished by a periodic grid structure. The measured maximum aperture efficiency reaches 55% and 58% in the desired lower and higher bands, respectively. The measured results of the antenna show superior performance, validating the design guidelines of the antenna topology.